2007
DOI: 10.1002/rra.976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow variability modification and hydraulics on invertebrate communities in the great fish river (Eastern Cape province, South Africa), with particular reference to critical hydraulic thresholds limiting larval densities of Simulium chutteri lewis (Diptera, Simuliidae)

Abstract: Flow patterns in the Great Fish River in the Eastern Cape province of South Africa have changed from being seasonal, with predictable no-flow periods during winter, to perennial following the completion of an inter-basin transfer scheme in 1977 to provide a regular supply of irrigation water. Simulium chutteri (Diptera: Simuliidae) consequently became a problem species of pestilential proportions, due to increased flow volumes and current velocities favouring this species. In this study, aquatic invertebrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…In our study, filtering taxa such as Simuliidae and the net-spinning Hydropsyche had rheophilic preferences similar to those observed in smaller German streams and elsewhere (e.g. Rivers-Moore et al, 2007). Moreover, our results are in agreement with those of Dolédec et al (2007), who showed that differences in hydraulic habitat preferences across surveys were stronger for generalists than for specialists.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, filtering taxa such as Simuliidae and the net-spinning Hydropsyche had rheophilic preferences similar to those observed in smaller German streams and elsewhere (e.g. Rivers-Moore et al, 2007). Moreover, our results are in agreement with those of Dolédec et al (2007), who showed that differences in hydraulic habitat preferences across surveys were stronger for generalists than for specialists.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, filtering taxa such as Simuliidae and the net‐spinning Hydropsyche had rheophilic preferences similar to those observed in smaller German streams and elsewhere (e.g. Rivers‐Moore et al. , 2007).…”
Section: Discussionsupporting
confidence: 84%
“…It is thus during the late winter to early spring (August to September) that the blackfly larvae develop with minimal biotic interference (de Moor, 1989), and this then favours exponential population increase at this time of the year. Assuming that some minimal flows are maintained it is assumed that the proposed flow controls will have minimal negative effects on hydropsychid populations, since this group was shown to prefer lower flow velocities (<0.8 m s À1 ) than S. chutteri (Rivers-Moore et al, 2007). If flow reductions could target the period when the hydropsychid population levels are at their lowest then maximum efficiency in keeping simuliid population levels in check can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Curve 9 was included in the analyses to illustrate the relationship between velocity and width in the upstream pool. While a limited hydraulic habitat is theoretically available to larval blackfly in the pool biotope (15% where velocities are in excess of 1 m s À1 ), the Froude numbers of these flows would be too low in practice for this biotope to be suitable as habitat, and blackfly larvae are typically absent (Rivers-Moore et al, 2007). The percentage of available hydraulic habitat was found to range between 0% and 90%, with a sharp inflection point for flows in excess of 2 m 3 s À1 , based on the integrals of curves 1-8 (Table II).…”
Section: Flow Analyses and Habitat Availabilitymentioning
confidence: 99%
See 1 more Smart Citation